0206 The longitudinal association between multiple job holding and long-term sickness absence among danish employees. an explorative study using register-based data. (21st August 2017) - Bouwhuis, Stef; Garde, Anne Helene; Geuskens, Goedele; Boot, Cécile; Bongers, Paulien; Beek, Allard van der
Abstract : Background: Multiple job holding (MJH) is common in many countries, but little is known about its (health) consequences. Our aim is to explore the longitudinal association between MJH and long-term sickness absence (LTSA) among Danish employees. Methods: We included employees (n=8, 968) who participated in the Danish Work Environment Cohort Study (DWECS), based on a representative sample of the Danish working population. Three dichotomous independent variables were created: MJH in general, combination MJH (i.e. second job as employee) and hybrid MJH (i.e. self-employed in second job). LTSA (≥5 weeks) was measured using the Danish Register for Evaluation of Marginalisation (DREAM) during 78 weeks of follow-up. Potential confounders included demographics, health, and work characteristics. Logistic regression analyses were performed to study whether LTSA was associated with MJH in general, combination MJH, and hybrid MJH. Interaction effects for gender, age, total working hours per week (≤37 or>37 hours a week) and shift work were tested. Results: In total, 11.7% (n=1, 048) of the respondents reported having multiple jobs and 7.6% (n=678) experienced LTSA during follow-up. After adjustment for confounders, no significant association between LTSA and MJH in general (OR=0.82), combination MJH (OR=0.81), or hybrid MJH (OR=0.83) was found. Among employees working more than 37 hours per week, combination MJH was associated with a higher likelihood of LTSA (OR=1.50). Conclusions: We did not find evidence for an increased likelihood of LTSA among multiple job holders. Future research should study the likelihood of LTSA among subgroups of multiple job holders, e.g. those working long hours.